Alice in Wonderland - Sutherland, T.T. 1978- (Penguin Group, 2010)
From Walt Disney Pictures and visionary director Tim Burton comes a magical re-imagining of one of the most beloved stories of all time. Mia Wasikowska stars as 19-year-old Alice, who returns to the whimsical world she first encountered as a young girl, reuniting with her childhood friends: the White Rabbit, Tweedledee and Tweedledum, the Dormouse, the Caterpillar, the Cheshire Cat, and of course, the Mad Hatter. Alice embarks on a fantastical journey to find her true destiny and end the Red Queen's reign of terror